E-learning Experiences and Future - Soomro, Safeeullah (IntechOpen, 2010)
This book is consisting of 24 chapters which are focusing on the basic and applied research regarding e‐learning systems. Authors made efforts to provide theoretical as well as practical approaches to solve open problems through their elite research work. This book increases knowledge in the following topics such as e‐learning, e‐Government, Data mining in e‐learning based systems, LMS systems, security in e‐learning based systems, surveys regarding teachers to use e‐learning systems, analysis of intelligent agents using e‐learning, assessment methods for e‐learning and barriers to use of effective e‐learning systems in education. Basically this book is an open platform for creative discussion for future e‐learning based systems which are essential to understand for the students, researchers, academic personals and industry related people to enhance their capabilities to capture new ideas and provides valuable solution to an international community.